Partie mniejszości węgierskiej na Słowacji w latach 1989-1998. Aktorzy, elity, wyborcy - Wojtas, Kinga (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
Celem artykułu jest pokazanie wielości i różnorodności partii węgier¬skich funkcjonujących w latach 1990-1998 w systemie partyjnym Słowacji, a zatem przed powstaniem w 1998 r. Partii Węgierskiej Koalicji - Strana mad’arskej koalicie (SMK). Tekst ten koncentruje się na odpowiedzi na pytania: 1) kim byli ich liderzy i elita partyjna - czy można mówić o ciągłości personalnej reprezentacji mniejszości od 1990; oraz 2) kto głosował na poszczególne partie mniejszości węgierskiej. Wąt¬kiem marginalnym, będzie refleksja na temat, jakie miejsce zajmowały analizowane partie w układzie rywalizacyjnym. Tekst też próbuje odpowiedź na pytanie, czy po¬wstanie SMK oznaczało intensyfikację konfliktu narodowościowego w słowackim systemie partyjnym.

The aim of the article is to show the multiplicity and diversity of Hungarian ethnic parties existing in the years 1990-1998 within the party system of Slovakia, before the emergence of the Hungarian Coalition Party - Strana mad’arskej koalicie (SMK) in 1998. This text focuses on answering the following questions: (1) who were the parties’ leaders and elites, and whether it is justified to talk about the continuity of personal representation of minorities since 1990; and (2) who voted for different Hun¬garian minority parties and whether their unification into the SMK brought with it an electoral bonus. An additional aspect of this is the position of the analyzed parties in the competitive system. The text also tries to answer the question of whether the creation of the SMK led to an intensification of the national split within the Slovakian party system.
The political parties of Hungarian minority in Slovakia, 1989-1998: actors, elites, electorate
Keywords: partie etniczne; Słowacja; mniejszość węgierska; elity; ethnic parties; Slovakia; Hungarian minority; party elites; election